1925
DOI: 10.1002/jlac.19254420113
|View full text |Cite
|
Sign up to set email alerts
|

Über die Konstitution der Grignardschen Magnesiumverbindungen. II

Abstract: Dio SchwelriickstGnde hattcn koksartiges Aussehen, wmen aber uicbt gebacken. Sie zeigten keinerlei Ltislichkeit in Alkali oder anderen LBmngsmitteln. Bei der Behandlung mit st:wker Salpetersiiure in der Warnie trat langsam L6sung ein, beim EingieBen in Wasscr wurden rotbraune Flocken ausge8lIt. Brornlauge baut die Schwehiickstande zu Bromoform und Tetrabromkohlenstoff ab. Beim Erhiteen der Schwelriickstande bis ZIX dunkler Rotglut werden weitere ganz geringe Tceinpngen und brennbare Gase abgegeben. A. Benzalde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1925
1925
1959
1959

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The ether layer w'as shaken with 5% sodium bicarbonate, washed with water, and dried over sodium sulfate. Distillation gave 1 g.), which was identified by its physical properties and the melting point of the 3,5-dinitrobenzoate as the same compound which was prepared from bromoacetone and methylmagnesium bromide (8).…”
Section: Methodsmentioning
confidence: 99%
“…The ether layer w'as shaken with 5% sodium bicarbonate, washed with water, and dried over sodium sulfate. Distillation gave 1 g.), which was identified by its physical properties and the melting point of the 3,5-dinitrobenzoate as the same compound which was prepared from bromoacetone and methylmagnesium bromide (8).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that reactions between covalent molecules are greatly facilitated by the presence of media or catalysts that are capable of producing coordination complexes (26). Interchanges between covalent bonds may occur as the final stage of the mechanism.…”
Section: Brch2coor>>clch2coor>cl2chcoor>cl8ccoormentioning
confidence: 99%